The Pattern of Carbohydrate Distribution of Accessory Sex Glands in Male Muntjac (Muntiacus muntjak muntjak) - Sri Wahyuni; Boni Anggara; Muslim Akmal; Hamny Hamny; Mustafa Sabri (Universitas Syiah Kuala, 2014)
The objective of this study was to investigate the pattern of carbohydrate distribution of accressory sex glands in male muntjac (Muntiacus muntjak muntjak) in the velvet antler stage. In macroanatomy observation, muntjac accessory sex glands consist of the ampulla, vesicular gland, pars diseminate prostat, and bulbourethral gland. The observation of neutral carbohydrate distribution has done by periodic acid Schiff (PAS) staining. In addition, acid carbohydrate was observed by using alcian blue (AB) pH2,5 staining. Result of this research showed that neutral and acid carbohydrate scattering in each accessories sex gland with different pattern. Neutral carbohydrate with medium (++) and high (+++) intensity reaction was found in the ampulla, vesicularis gland, and bulbourethral gland and strong in prostat gland. The acid carbohydrate with low (+) and medium (++) intensity reaction was observed in the ampulla, low in vesicularis gland, and negative in prostat and bulbourethral glands. In conclusion, the neutral carbohydrate was found dominantly on surface of all accessory sex glands of male muntjac in velvet antler stage with highest concentration and intensity of colour in prostat gland.Key words: carbohydrate, accessory sex glands, muntjac (Muntiacus muntjak muntjak)